Pengaruh Penambahan Serat Bambu Terhadap Kuat Tarik dan Kuat Tekan Beton - Trimurtiningrum, Retno (JHP17 (Jurnal Hasil Penelitian), 2018)
Concrete is one of construction material that has been used widely for many years.The advantages of using concrete as contruction materials are it has high compressive strength,easy to be molded, no need professional labours and the constituent materials of concrete arecheap and easy to get. Beside of those advantages, concrete also has disadvantage such as haslow tensile strength. Its tensile strength is only about 10% from its compressive strength. Manyprevious research has been conducted to increase the tensile strength of concrete. In late 1960s,fiber concrete has been researched to be the solution to increase the tensile strength of concrete.Types of fiber concrete are steel fiber, glass fiber, synthetic fiber and natural fiber. Naturalfiber concrete such as bamboo has low manufacturing cost than the other types of fiber. Theaimed of this research is to investigate the influence of bamboo fiber concrete on the tensilestrength and the compressive strength of concrete. The percentage of bamboo fiber were variedfrom 0%, 1%, 2% and 3% by cement material. The test results showed that bamboo fiberconcrete increase the tensile strength test and compressive strength test result. The highesttensile strength was 12,4 MPa in 28 days obtained by mixture that contained 2% of bamboofiber. The highest compressive strength concrete was 28,3 MPa in 28 days from the mixtureswith 1% of bamboo fiber.Keywords: concrete, fiber concrete, bamboo fiber concrete, compressive strength, tensilestrength